Effect of popular songs from the reminiscence bump as autobiographical memory cues in aging: a preliminary study using EEG - Martínez-Saez, Maria Cruz; Ros, Laura; López-Cano, Marco; Nieto, Marta; Navarro, Beatriz; Latorre, Jose Miguel (Frontiers in Neuroscience, 2024)
Introduction: Music has the capacity to evoke emotions and memories. This capacity is influenced by whether or not the music is from the reminiscence bump (RB) period. However, research on the neural correlates of the processes of evoking autobiographical memories through songs is scant. The aim of this study was to analyze the differences at the level of frequency band activation in two situations: 1) whether or not the song is able to generate a memory; and 2) whether or not the song is from the RB period. Methods: A total of 35 older adults (22 women; age range: 61-73 years) listened to 10 thirty-second musical clips that coincided with the period of their RB and 10 from the immediately subsequent five years (non-RB). To record the EEG signal, a brain-computer interface (BCI) with 14 channels was used. The signal was recorded during the thirty-seconds of listening to each music clip. Results: The results showed differences in the activation levels of the frequency bands in the frontal and temporal regions. It was also found that the non-retrieval of a memory in response to a song clip showed a greater activation of low frequency waves in the frontal region, compared to the trials that did generate a memory. Discussion: These results suggest the importance of analyzing not only brain activation, but also neuronal functional connectivity at older ages, in order to better understand cognitive and emotional functions in ageing.